Exploring entrepreneurial readiness of youth and startup success components: Entrepreneurship training as a moderator - Seun Azeez Olugbola (Journal of Innovation & Knowledge (JIK), 2017)
From the behavioral perspective, this study analyzed the entrepreneurial readiness of youth in terms of opportunity identification, motivational factors, resources, and entrepreneurial ability. The study examined the effect of entrepreneurship training on young people's readiness to engage in entrepreneurial activity and the components behind successful startups. SEM was applied to a sample of 490 students from the Universiti Sains Islam Malaysia. The findings highlight the positive effect of opportunity identification, motivation, and resources on entrepreneurship and the central role of entrepreneurship training in all factors, including entrepreneurial ability. The role of entrepreneurship training implies that young individuals are able to develop their entrepreneurial ability. The study thus shows the individual's ability to change over the course of a lifetime. For individuals interested in the startup process, this study provides information capable of influencing their new business ventures.
Keywords: M13; O31; C91; L24; J24; M53; 650; Entrepreneurial readiness; Opportunity identification; Motivation; Resources; Entrepreneurial ability; Entrepreneurship training